2012
DOI: 10.1117/1.jbo.17.9.097009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enamel abrasion, salivary pellicle, and measurement angle on the optical assessment of dental erosion

Abstract: Abstract. The present study assessed the effects of abrasion, salivary proteins, and measurement angle on the quantification of early dental erosion by the analysis of reflection intensities from enamel. Enamel from 184 caries-free human molars was used for in vitro erosion in citric acid (pH 3.6). Abrasion of the eroded enamel resulted in a 6% to 14% increase in the specular reflection intensity compared to only eroded enamel, and the reflection increase depended on the erosion degree. Nevertheless, monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 81 publications
6
33
0
1
Order By: Relevance
“…Linear decrease and increase of the backscattered light intensity during demineralization and remineralization processes were reported by Kishen et al 18 Change of the specular and diffuse reflection intensities during erosion progression was investigated in our previous in vitro studies. 19,20 Particularly, sharp decay of the specular reflection was observed already in the early stages of enamel erosion in vitro, while the less pronounced increase of the diffuse reflection intensity was measured, which correlated well with the results of Thomas et al 17 Further investigation revealed a strong correlation between the decrease of the specular reflection and continuous surface roughening. 19 Significant change of the specular reflection was detected even in eroded and abraded surfaces.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…Linear decrease and increase of the backscattered light intensity during demineralization and remineralization processes were reported by Kishen et al 18 Change of the specular and diffuse reflection intensities during erosion progression was investigated in our previous in vitro studies. 19,20 Particularly, sharp decay of the specular reflection was observed already in the early stages of enamel erosion in vitro, while the less pronounced increase of the diffuse reflection intensity was measured, which correlated well with the results of Thomas et al 17 Further investigation revealed a strong correlation between the decrease of the specular reflection and continuous surface roughening. 19 Significant change of the specular reflection was detected even in eroded and abraded surfaces.…”
Section: Introductionsupporting
confidence: 78%
“…19,20 This study presents a next step toward the To make this step, a handy and simple instrument was required based on the same optical system utilized previously. 19 Thus, the entire optics was miniaturized into a pen-size instrument, though the angles of incidence and reflection had to be reduced to 23 deg (versus 45 deg in the original prototype setup 19 ) to provide so small instrument head size that it could access all positions inside the oral cavity (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,24 Na sequência, caso o desafio ácido persista, tem-se início o segundo estágio, no qual, devido à continua difusão dos íons hidrogênio para o interior do esmalte, ocorre uma desmineralização numa camada inferior, próxima a superfície, aprofundando a camada amolecida. 27,48 Assim, a magnitude do desafio ácido se torna maior que a capacidade de troca de minerais entre o dente e fluidos da cavidade oral, resultando, portanto, num desequilíbrio do processo de des/remineralização. Dessa forma, o esmalte vai sendo perdido, camada por camada, progressivamente, até o aparecimento do desgaste erosivo clínico.…”
Section: Erosão Em Esmalteunclassified